Realisme Magis pada Cerita Alaming Lelembut dalam Majalah Panjebar Semangat Edisi Januari-Mei Tahun 2025 - Dwi Linda Novaviana; Rahma Ari Widihastuti; Dandung Adityo Argo Prasetyo (Khatulistiwa: Jurnal Pendidikan dan Sosial Humaniora, 2025)
Javanese society continues to believe that the mystical world coexists with everyday life, as reflected in Javanese literary works published in Panjebar Semangat, particularly in the Alaming Lelembut column. This study examines forms of magical realism in 19 stories published from January to May 2025 using Wendy B. Faris’s theory, which includes the Irreducible Element, the Phenomenal World, Unsettling Doubt, Merging Realism, and the Disruption of Time, Space, and Identity. The findings reveal that; (1) the Irreducible Element appears through magical objects, events, characters, and myth-based beliefs that cannot be explained empirically. (2) The Phenomenal World depicts realistic settings of time, place, objects, and events, while (3) Unsettling Doubt creates ambiguity between the real and the mystical for readers. (4) Merging Realism is shown through the intrusion of spirits into the real world. (5) Disruptions of time, space, and identity blur the boundaries between reality and the supernatural through temporal reappearances of the dead, rapid spatial shifts, and transformations of identity. This study demonstrates that Javanese literature serves as a medium for preserving local wisdom while simultaneously facilitating contemporary cultural transformation.